Patriarchy system in the accounting profession in Malaysia from the perspective of women accountants. - Johari, Jalila; Abdul Hamid, Erwina Norhaznina; Arshad, Azizan (KnE Publishing, 2024)
This paper aimed to explore the patriarchal system in the accounting profession that had prevailed and oppressed female accountants. Women in accounting professions that cantered the organisational structure and education were used in this research, as well as main constructs such as lack of working experience as a woman accountant, gender discrimination between man and woman, and the suitability of women to choose a career as an accountant. The data was collected by distributing questionnaires to 64 female accountants around Malaysia with experience work of more than five years. Findings showed that the discrimination of gender between women and men and the suitability of women to choose a career as an accountant has a significant influence on the patriarchal system in the accounting profession in Malaysia. This study is the first in Malaysia and represents a strong implication for policies and their evaluation. It identifies the patriarchy as a social and ideological structure that sees women as inferior to men (patriarchs). In a society with the unfair power of men and women, Patriarchy imposes stereotypes about masculinity and femininity.